Before and After Radical Prostate Surgery: Information and Resource Guide - Virginia Vandall-Walker (Athabasca University Press, 2008)
Before and After Radical Prostate Surgery is a research-based, comprehensive, and comprehensible resource on prostate surgery in Canada. Aimed at men with concerns about prostate surgery and their partners, this invaluable guide includes chapters on preparing for prostate surgery, the surgery itself, recovery in hospital and at home, a list of recommended resources, and special sections to record personal notes and important contact information.